Family Support and Glucose Control Related to Microvascular Complications Symptoms - Wardani, Alfiah Kusuma; Isfandiari, Muhammad Atoillah (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTDiabetes Mellitus is a chronic disease whose prevalence continues to increase. WHO predicts that diabetes will be 7 major diseases that will cause the death in 2030. Many people with diabetes are not aware ofÂ  it so that they get complications. The increasing number of people with diabetes mellitus who develop complications because of the bad controlling of blood sugar levelsÂ  and the lack of support from family. The Complications were observed in this study is microvascular complications. This study aims to analyze between family support and control blood sugar levels with the incidence of microvascular complications in the patients with symptoms of diabetes mellitus in the Community Health Center Jagir Surabaya.This research uses analytic observational study sample of patients with diabetes mellitus who had diabetes mellitus â¥ 5 years as many as 34 samples. The Sampling was done by the simple random sampling, while the data analysis was done by the Chi Square test.The results showed that there was no relationship between family support with symptoms of microvascular complications (p=0.069), but there is a relationship between the control of blood sugar levels with symptoms of microvascular complications (p=0.002).The Microvascular symptoms that are often experienced by people with diabetes mellitus in the Community Health Center Jagir is symptomatic neuropathy complications . The proportion of patients with diabetes mellitus who received family support at 55.9%, whileÂ  the patients with diabetes mellitus who control the blood sugar levels well totaling 17 respondents. It is expected that people with diabetes mellitus to control eating diet and regular exercise.Â Keywords : Family support, blood sugar levels control, symptoms of microvascular complications.